Proposta de intervenção motora e treino de alcance manual para a promoção do desenvolvimento motor e do alcance manual em lactentes abrigados - Cabral, Thais Invenção (Universidade Federal de São Carlos, 2017)
Introduction: In the first year of life, exploration of the environment allows the infant to learn about the ability to act and use resources of the environment, in order to perform adaptive actions. A stimulating environment favors motor development, while deprivation of stimuli, can cause motor disadvantages in reaching, as well as in gross motor development. Objectives: Study 1) to systematically synthesize evidences of motor intervention types to minimize the impacts of orphanage in infants and children motor development and to verify the effectiveness of these interventions; Study 2) to evaluate the gross motor development of orphaned infants and compare them with non-orphaned infants; Study 3) to verify if a protocol of motor intervention is capable of promoting quantitative changes in the gross motor development of orphaned infants; Study 4) to verify the influence of a training in the reaching of orphaned infants. Methods: Study 1) The searches were performed in PubMed, Scopus, Cochrane, Scielo, Lilacs and Embase databases and through direct searches in article references located in the databases. For the methodological quality assessment, were used a Physiotherapy database (PEDro) and a Newcastle-Ottawa quality assessment scale (NOS); Studies 2, 3, 4) This is a cross-sectional study. Twenty-nine infants (study 2) / 28 infants (studies 3 and 4) were divided into 2 groups: experimental group (n = 13 / n = 12) composed by orphaned infants and the comparison group (n = 16) composed by healthy infants non-orphaned, aged 6 to 7 months. Motor development was assessed using Alberta Infant Motor Scale (AIMS). The reaching was evaluated through the kinematic analysis of the following variables: trunk displacement, movement duration, deceleration index, retirement index, peak velocity, movement units and mean velocity. Infants in the experimental group received a motor intervention protocol (3) and a training for reaching (4) during 2 weeks. A mixed variance analysis was aplied to analyze an interaction between main effects of groups and time. Results: 1) Three articles were eligible for the results synthesis from 123 identified records in the initial searches. Two studies presented the design of a randomized clinical trial and one was a prospective longitudinal study. The two randomized clinical trials presented good methodological quality and the longitudinal study had low methodological quality; 2) There were differences between groups for prone score (p = 0.000046); supine score (p = 0.009) sitting score (p = 0.002) total score (p = 0.000126) and percentile (p = 0.000385); 3) There was difference in all postures in the pre-intervention: prone (F [2, 27] = 29,386; (p <0.0001), supine (F [2, 27] = 15,830, p = 0,0001), sitting (F [2, 27] = 12,025, p = 0,000) and in standing posture (F [2,27] = 5.322, p = 0.008). In the total score there was significant intra-group difference (F [2, 27] = 28,188; p = 0.0001), as well as in the percentile (F [2, 27] = 25,407; p = 0.0001); 4) There was a significant group*time interaction for the deceleration index variable (F [1.26] = 3.87, p = 0.02, η2 = 0.13). For the retirement index variable (F [2.52] = 4.45, p = 0.02, η2 = 0.15) and movement unit (F [2.52] = 3.42, p = 0, 04, η2 = 0.11) there was a significant effect of time. Discussion: The mechanisms of motor development of orphaned infants are few investigated. However, in this study, a motor intervention protocol and reaching training, were capable of promoting quantitative changes in the development of orphaned infants. Therefore sensory-motor experiences seem to favor an overcoming of intrinsic limitations, as well as environmental restrictions. Conclusion: The scientific community could turn to intervention studies for orphaned infants, as the number of this population increases each year because of the world poverty condition, the number of users of illicit drugs and the increase of natural disasters. It is a matter of public health.
Keywords: Lactentes; Abrigo; Desenvolvimento Infantil; Habilidades motoras; Infants; Orphaned; Child Development; Grasp; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL